Insecticidal effect of oregano (Origanum vulgare L. ssp. hirtum Ietswaart) on bean weevil (Acanthoscelides obtectus Say) - Baricevic, C.; Milevoj, L.; Borstnik, J. (International Journal of Horticultural Science, 2001)
The effectiveness of drug plant and of essential oil of oregano (Origanum vulgare L. ssp. hirtum Ietswaart) against the adults and egg hatching of bean weevil (Acanthoscelides obtectus Say) was studied in laboratory trials in order to screen for a new potential insecticide in the control of this granary pest of beans. The adult mortality as well as oviposition and hatching capabilities were evaluated after 6 days of treatment of beans cv. `Berggold' (55 g) in Petri dishes by powdered drug (0.33 g, 0.66 g, 1.0 g and 2.0 g) and by equivalent amounts of essential oil (5 ill, 10 15 ill and 30 ill). Oregano essential oil showed both fumigant and contact toxicities to bean weevil, the later being more potent. When considering fumigant toxicity, insecticidal effect (mortality rate 82.5%) was observed 6 days after application of high concentrations of oregano essential oil (150 Al per 55 g of beans). When considering contact toxicity, both oregano drug plant and essential oil at all tested concentrations significantly increased the bean weevils' mortality rates with comparison to the controls. Also, egg laying and hatching were inhibited after treatment of bean weevil with powdered drug plant or with essential oil at all tested concentrations. Insecticidal effect of drug plants issuing from two different stocks depended on their essential oil contents. Essential oils (5 pi, 15 pi and 30 IA per 55 g of beans) induced 100% mortality of bean weevil population when applied directly to the surface of beans (55 g) in Petri dishes. The content of essential oil in oregano and oregano-based preparations for insecticidal use is proposed as a parameter for quality control purposes.